Determinants of Government Characteristics and Audit Findings on Local Government Financial Performance - Mahendro Sumardjo; Febriana Dwi Jayanti (Information Management and Business Review, 2021)
This study is based on the low success of local governments' financial performance in West Java Province, as evidenced by the fact that financial reports of local governments that receive unqualified opinions are still being found. The detection of numerous frauds in local governments is responsible for the majority of incidents of poor financial performance in local governments. Local government financial performance is related to local government size, dependence on central government, local spending, and audit findings. The purpose of this study was to examine the influence of local government characteristics and audit findings on the financial performance of local governments. Techniques analyzing data used regression model selection test with STATA version 16. This study builds on agency theory to develop a conceptual framework that connects local government size, dependence on central government, local expenditure, audit findings, and financial performance. The results of this study show that the size of local government, local spending has a significant effect on local government financial performance based on independence ratio and operating expenditure activity ratio, local government financial performance is unaffected by the dependence of central government or audit findings. Contributions to the West Java Provincial Government are required to be taken into account when making decisions and policies for the improved financial performance of local government.